Coaching Quran Recitation for Teenagers with Muqri' at the Quran Boarding School - Ahiruddin Rangkuti; Meyniar Albina (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
This study investigates the role of muqri’ in guiding Qur’anic recitation (tilawah) among adolescents at Pondok Qur’an Hj. Adam Lubis and Hj. Kartini Batubara, Medan, Indonesia. Adolescence is a critical stage in character and spiritual development, where Qur’anic education contributes to shaping both technical recitation skills and moral values. However, limited research has examined how muqri’ as experts in qira’at influence adolescent learning processes and outcomes. The purpose of this research is to explore the methods employed by muqri’, assess their impact on students’ technical and spiritual development, and evaluate the effectiveness of talaqqi and talqin approaches in Qur’anic recitation training. Using a qualitative case study design, data were collected through participatory observation, in-depth semi-structured interviews with one senior student and two muqri’, and documentation analysis. The data were analyzed using Miles and Huberman’s interactive model, including data reduction, data display, and conclusion drawing. Trustworthiness was ensured through triangulation, member checks, and audit trails following Lincoln and Guba’s criteria. Findings show that muqri’ play a multidimensional role as instructors, role models, and spiritual mentors. The talaqqi method, characterized by direct teacher-student interaction, proved effective in correcting errors immediately and fostering motivation. The talqin process further enriched learning by integrating spiritual practices with technical mastery. Students reported increased fluency, better tajwid application, and stronger motivation to pursue excellence in Qur’anic recitation, including aspirations to compete internationally. In conclusion, this study highlights the essential role of muqri’ in developing both recitation skills and spiritual values, offering a replicable model for Qur’anic education in similar institutions.